Pengaruh Faktor Lingkungan Eksternal dan Internal terhadap Strategi Supply Chain Management Agroindustri - Dina Kartika Sari; Anita Qur’ania (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The agricultural product processing industrial sector, particularly the agro-industry in the food and beverage sector, significantly contributes to Indonesia’s national income. The consumption pattern of the agro-industrial community has changed over the past ten years. Previously, consumers’ preference for purchasing food and beverages was 38.9%, but this reduced to 36.7% in 2018. Due to shifting customer demand trends, this consumption issue is one that the environment outside the organization is to blame for. The supply chain management plan is one of the environmental concerns the organization has considered in its strategy. In the food and beverage agro-industry in Malang City, this study aims to ascertain the impact of ecological factors on supply chain management strategies and the existence of mediating variables, specifically internal factors that have an indirect relationship between external factors and supply chain management strategies. With a path coefficient of 0.212 0.688 and a P-value of <0.001, the WarpPLS SEM analysis method produced results that showed both internal and external factors had an impact on the supply chain management strategy despite internal factors having a more minor effect than external factors. To sustain client loyalty, internal variables must continue to match customer demand when there is an increase in the number of customers. The priority for company improvement is more on the system within the company.